Perspectives on blended learning through the on-line platform, LabLessons, for Chemistry - Teeba Jihad; Edward Klementowicz; Patrick Gryczka; Chappel Sharrock; Macrae Maxfield; Yougjun Lee; Jin Kim Montclare (OmniaScience, 2018)
The effectiveness of blended learning was evaluated through the integration of an online chemistry platform, LabLessons. Two modules, Titration and Formation of Hydrogen, were designed by college mentors alongside classroom chemistry teachers to engage and allow high school students to better comprehend these scientific topics.  The pre-lab modules introduced the students to experiments they were expected to perform in class the following day. The modules consisted of an introduction as well as either a visualization and/or simulation specific to each topic. Students and teachers who utilized LabLessons were surveyed to establish a preliminary research on the use of technology in classrooms. Student and teacher surveys demonstrated LabLessons to be an interactive and helpful tool to improve students' understanding of conceptual ideas.